Carriage of multidrug-resistant organisms in a tertiary university hospital in Albania—a point prevalence survey. Issue 1 (December 2016) - Parascandalo, Falzon; Zarb, P.; Tartari, E.; Lacej, D.; Bitincka, S.; Manastirliu, O.; Nika, D.; Borg, M.
Abstract Background Antimicrobial resistance has been recognised as a serious global Public Health problem. Prevalence of Multiple-Drug-Resistant (MDR) organism carriage in Albania is largely unknown since no national surveillance system is in place and few publications are accessible in the literature. Methods A 1-day point-prevalence-survey (PPS) screening for nasal methicillin-resistant Staphylococcus aureus (MRSA) and rectal MDR Gram-negative carriage was carried out at the high-dependency wards in the country's only tertiary care hospital, in Tirana. Results A total of 106 nasal and 104 rectal swabs were collected. 14.2 % of patients (95 % Confidence Interval [95 CI]: 8.1–22.3 %) were MRSA nasal carriers. Resistance to aminoglycosides and fluoroquinolones was common in these isolates (≥80 %) but no resistance was identified against glycopeptides, nitrofurantoin and the relatively newer agents, tigecycline and linezolid. Fifty Enterobacteriaceae isolates were cultivated from 33 of 104 screened patients (31.7 % [95 CI: 22.9–41.6 % 95 CI]). The prevalence of Extended Spectrum Beta-Lactamase (ESBL) production in Enterobacteriaceae was 41.3 % (95 CI: 31.8–51.4 %). The two more commonly isolated Enterobacteriaceae wereE. coli ([n = 28], 24 ESBL positive; 1 AmpC positive and 3 without an identified mechanism of resistance) andKlebsiella pneumoniae ([n = 13], all ESBL positive; 1 also AmpC and metallo-β-lactamase (MBL) positive). Susceptibility to carbapenems (≥98 %), fosfomycin (90 %) and amikacin (70 + 20 % intermediate) was high but a high level of resistance to all other agents tested was noted. Non-fermenting Gram-negative bacilli were less commonly isolated 22 isolates:Acinetobacter baumannii (9);Pseudomonas aeruginosa (8) andStenotrophomonas maltophilia (5). Conclusion Although a significant rate of MRSA carriage was identified, the main resistance challenge in Albania appears to be linked with Gram-negative organisms, particularly ESBL in Enterobacteriaceae.